2018
DOI: 10.3390/insects9020051
|View full text |Cite
|
Sign up to set email alerts
|

Cyanogenesis in Arthropods: From Chemical Warfare to Nuptial Gifts

Abstract: Chemical defences are key components in insect–plant interactions, as insects continuously learn to overcome plant defence systems by, e.g., detoxification, excretion or sequestration. Cyanogenic glucosides are natural products widespread in the plant kingdom, and also known to be present in arthropods. They are stabilised by a glucoside linkage, which is hydrolysed by the action of β-glucosidase enzymes, resulting in the release of toxic hydrogen cyanide and deterrent aldehydes or ketones. Such a binary syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 214 publications
(334 reference statements)
0
49
0
Order By: Relevance
“…Whereas sequestration of cyclopentenyl CNglcs has been reported only in butterflies of the Heliconiinae subfamily, biosynthesis of linamarin and lotaustralin has been demonstrated in several species of butterflies and moths belonging to many taxonomically distinct families, such as Zygaenidae, Limacodidae, Heterogynidae, Nymphalidae, and Lycaenidae (Davis & Nahrstedt, ; Nahrstedt, ; Zagrobelny, Castro et al, ). The biosynthetic pathway in the burnet moth Z. filipendulae is encoded by the genes ZfCYP405A2 , ZfCYP332A3, and ZfUGT33A1 (Jensen et al, ) and putative homologues of these P450s have been found in the genome of the postman butterfly H. melpomene, HmCYP405A4 , HmCYP405A5, HmCYP405A6, and HmCYP332A1 (Chauhan et al, ) and in other Heliconius species (Zagrobelny, Jensen, Vogel, Feyereisen, & Bak, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas sequestration of cyclopentenyl CNglcs has been reported only in butterflies of the Heliconiinae subfamily, biosynthesis of linamarin and lotaustralin has been demonstrated in several species of butterflies and moths belonging to many taxonomically distinct families, such as Zygaenidae, Limacodidae, Heterogynidae, Nymphalidae, and Lycaenidae (Davis & Nahrstedt, ; Nahrstedt, ; Zagrobelny, Castro et al, ). The biosynthetic pathway in the burnet moth Z. filipendulae is encoded by the genes ZfCYP405A2 , ZfCYP332A3, and ZfUGT33A1 (Jensen et al, ) and putative homologues of these P450s have been found in the genome of the postman butterfly H. melpomene, HmCYP405A4 , HmCYP405A5, HmCYP405A6, and HmCYP332A1 (Chauhan et al, ) and in other Heliconius species (Zagrobelny, Jensen, Vogel, Feyereisen, & Bak, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to H. sapho , all species of the sara‐sapho group feeding on Astrophea plants contain only epivolkenin, and it is possible that they may have lost the ability to synthesize aliphatic CNglcs to become more specialized in sequestration as suggested by Engler‐Chaouat and Gilbert (). Yet, apparently functional P450 genes associated with the biosynthesis of linamarin and lotaustralin are present in the genome of H. sapho (Zagrobelny, Castro et al, ) suggesting that the lack of biosynthesis could be due to transcriptional and/or translational mechanisms. On the other hand, large amounts of linamarin and lotaustralin were found in H. sara and H. charithonia which, although belonging to the same group as H. sapho , are not Astrophea specialists but Decaloba specialists .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larvae of most Heliconiini species synthesize CGs de novo (Wray, Davis, & Nahrstedt, ), but many sequester CGs from the host plants (Engler et al, ). Both synthesis and sequestration of CGs are only observed in Zygaenidae (burnet moths) and Heliconiini, two clades where aposematic color patterns have evolved (Zagrobelny, Castro, Møller, & Bak, ). So far, Heliconiini have been reported to sequester five cyclopentenoid CGs from Passiflora ; the diastereoisomers tetraphyllin B and epivolkenin, tetraphyllin A, gynocardin, and dihydrogynocardin (Figure ) (Castro, Zagrobelny, et al, ; Engler et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Larvae of most Heliconiini species synthesize CGs de novo (Wray, Davis, & Nahrstedt, 1983), but many sequester CGs from the host plants (Engler et al, 2000). Both synthesis and sequestration of CGs are only observed in Zygaenidae (burnet moths) and Heliconiini, two clades where aposematic color patterns have evolved (Zagrobelny, Castro, Møller, & Bak, 2018).…”
Section: Introductionmentioning
confidence: 99%